Pengamanan Data Inventaris Menggunakan Algoritma Kriptografi Tripple DES dan RC4 - Hutauruk, Simon Ricardo Valentino; Khairani, Mufida (Forum Kerjasama Pendidikan Tinggi, 2025)
Data security is an essential aspect of information management, particularly inventory data, which includes assets, supplies, and logistics. If this data is misused, it can lead to financial and operational losses. This research develops an inventory data security system that utilizes the Triple Data Encryption Standard (Triple DES) and Rivest Cipher 4 (RC4) cryptographic algorithms. The system is capable of protecting the item name and price columns in the inventory, as well as providing a decryption feature for encrypted data. Additionally, the security of the application is strengthened through user authentication. Combining these two cryptographic algorithms offers an optimal security solution, considering system performance and speed without disrupting daily operations.